Uma infraestrutura de gerência de conhecimento em organizações de software aplicada à gestão de riscos - Coelho, Alexandre Guilherme Nicco (2010)
In an organization, many people start to work, perform their activities and live new experiences. As a consequence of that, these people acquire knowledge that can be used in future situations. However, the acquired knowledge is maintained only in the minds of these people and when they leave the organization, organizational knowledge is also lost. Soon, newcomers in the organization can repeat the same mistakes that others have committed, and this could be avoided. Organizational knowledge has become increasingly important. Manage this knowledge is not a simple task, but many benefits can be achieved when this is done, in special, the improvement of the business process performance. It is important for the organization to define strategies to capture, store, deliver and use that knowledge when needed. Even when it is not possible to document the knowledge gained by members of the organization, it is important that the organization knows their abilities and skills so that, when problems arise, most suitable persons can be found to solve them. Moreover, communication support mechanisms can be very useful for interaction among members of the organization, besides being used as a tool for sharing and generation of knowledge. Among the activities of the software process, one that stands out is risk management. Managing risk in software projects is not an easy task and requires knowledge and experience. Thus, experience gained in past projects can be very useful for risk management of new projects. The main objective of this work is to develop a knowledge management infrastructure for software organizations. This infrastructure is used to support activities of risk management of software projects.